Karlodinium zhouanum, a new dinoflagellate species from China, and molecular phylogeny of Karenia digitata and Karenia longicanalis (Gymnodiniales, Dinophyceae). Issue 4 (1st July 2018) - Luo, Zhaohe; Wang, Lei; Chan, Leo; Lu, Songhui; Gu, Haifeng
Abstract: Little is known about the diversity and biogeography of the toxigenic dinoflagellate genera Karlodinium and Karenia because their cells are unarmoured and often small. We isolated single cells from Chinese waters to establish five Karlodinium cultures, and carried out single-cell polymerase chain reactions of eight cells of Karlodinium and Karenia isolated directly from field samples. We also obtained large-subunit (LSU) ribosomal DNA and internal transcribed spacer (ITS) sequences from the same samples used for descriptions of Karenia digitata and Karenia longicanalis . Five cultures of Karlodinium from the South China Sea and Yellow Sea of China were established and subjected to light, scanning electron, and transmission electron microscopy. These strains had a sulcal intrusion, a short apical groove, and six chloroplasts, each with an internal lenticular pyrenoid, but lacked a ventral pore. Pigment analysis showed that fucoxanthin was the main accessory pigment. On the basis of unique morphology and corroboration by molecular phylogeny, these strains were described as Karlodinium zhouanum sp. nov . LSU or ITS sequences (or both) of another eight cells revealed the presence of Karlodinium australe, Karenia longicanalis, and K. papilionacea in the East China Sea for the first time. LSU sequences showed that Karenia digitata differed from Karlodinium decipiens at only one position (99.86% similarity), and Karenia longicanalis differed from K. umbella at only four positions (99.45% similarity). Maximum-likelihood and Bayesian inference analyses supported the classification of Karenia digitata within Karlodinium, and demonstrated that presence of a ventral pore was not a reliable generic character for Karlodinium . Our results also indicated that LSU sequences might be too conservative to differentiate species of Karenia and Karlodinium .